Pengaruh Penggunaan Media Peta dalam Meningkatkan Hasil Belajar Kognitif Siswa di SDN Negri 1 Mendana: The Effect of Using Map Media in Improving Students' Cognitive Learning Outcomes at SDN Negri 1 Mendana - Lalu. A. Hery Qusyairi (Pendidikan Al-Gafari, 2026)
Media can be used to simplify or facilitate learning for students in abstract subjects. Media is also believed to help teachers simplify and overcome communication problems they encounter when teaching a given topic. This study aims to determine the effect of using map media in improving students' cognitive learning outcomes at SDN Negri 1 Mendana. This type of research uses a quantitative approach. This quantitative approach is an approach that describes or illustrates a problem or event using numbers or results in non-descriptive form. The results of the study found that the application of map media in improving students' cognitive learning outcomes at SDN Negri 1 Mendana experienced the expected increase. Maps are a perfect medium for enhancing student knowledge. Of the 20 samples used in the study, approximately 55% of maps significantly impacted student knowledge.